Coronavirus Awareness and Mental Health: Clinical Symptoms and Attitudes Toward Seeking Professional Psychological Help - Landa-Blanco, Miguel; Landa-Blanco, Ana; Mejía-Suazo, Claudio J.; Martínez-Martínez, Carlos A. (Frontiers in Psychology, 2021)
The current study analyzed the relationship between Coronavirus (COVID-19) Awareness, mental health and willingness to seek professional psychological help. This was made through a quantitative approach, using online questionnaires to collect data from 855 subjects. The questionnaires included the Brief Symptom Inventory (BSI-53) to measure mental health indicators, the Attitudes Toward Seeking Professional Psychological Help Scale–Short Form, and the Coronavirus Awareness Scale-10 (CAS-10). An Exploratory Factor Analysis suggests that three factors underlie the CAS-10: Coronavirus Concern, Exaggerated Perception, and Immunity Perception. Results indicate a significant positive correlation between Coronavirus Concern and both general anxiety and phobic anxiety symptoms. Immunity Perception is positively related to paranoid ideation and psychotic symptoms. A Mediation Analysis determined that Coronavirus Concern has a significant positive direct effect on Openness to Seeking Psychological Treatment (OSPT), while Exaggerated Perception and Immunity Perception scores have significant direct negative effects on the Value and Need in Seeking Treatment (VNST) scores. Indirectly, the relationship between Coronavirus Concern and OPST is significantly mediated by anxiety symptoms. Similar results were found for the VNST subscale. There is a negative significant effect of Immunity Perception over OSPT mediated by Paranoid Ideation. However, the overall model only achieved small r2 coefficients for the OSPT (0.060) and VNST (0.095) scores. Comparisons in Coronavirus Awareness between sex, age, and the presence of children and older adults at home were also made. These results are discussed regarding their practical implications for mental health providers and policymakers.